A thin orogenic wedge upon thick foreland lithosphere and the missing foreland basin - Garfunkel, Zvi; Greiling, Reinhard O. (Geologische Rundschau, 1998)
Along the Caledonian front in central Scandinavia, the expected peripheral or pro-foreland basin is neither physically present nor are there any significant traces in the sedimentary record. In order to explain and quantify this situation, the authors assess the major geometric and mechanical constraints on the Caledonian orogenic wedge and model the orogenic load and its influence on the foreland lithosphere of Baltica. Geologic and geophysical data show a strong foreland lithosphere with a flexural parameter (α) of approximately 100 km. The shape of the orogenic wedge and its critical taper angle are dependent mainly on basal friction and wedge strength. In the external part organic-rich black shales provide a low-friction horizon both at the basal detachment surface and within the wedge itself. The more internal part of the wedge is composed of metamorphic and crystalline rocks, which cooled and strengthened prior to thrusting. As a result, the external part of the wedge had a lower strength and a smaller critical taper angle than its internal part, so the orogenic load is upward concave. Modelling of the effect of such a load on the Baltica lithosphere shows a very small depression in front of the load (2 km). The flexural depression produced by the main part of the orogenic load is filled up by the thickening thrust-and-fold belt, so that there is little space left for a foreland basin. These results imply that the missing foreland basin in front of the central Scandinavian Caledonides is not due to subsequent erosion, but is a primary feature.